Traumatic avulsion of female urethra: a case report - Mishra, Vineet; Goel, Sugandha; Agarwal, Himani; Shah, Kunur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Traumatic female urethral avulsion in the absence of a pelvic fracture is an exceedingly rare entity. We report a case of 26 years old lady with crescentic tear of anterior urethra from pubic symphysis. Management consisted of primary urethral repair.